Tidy's physiotherapy - Porter, Stuart B. (Physiotherapy essentials, 2011)
Whether they're just starting out or about to go on placement or need to look up something for an assessment, this title intends to meet the needs of physiotherapy students. It includes a DVD ROM, which contains sections on musculoskeletal tests, massage and exercise, and graphics which can be used for revision, presentations and even teaching